Fetal Liver Bisphenol A Concentrations and Biotransformation Gene Expression Reveal Variable Exposure and Altered Capacity for Metabolism in Humans. Issue 2 (3rd December 2012) - Nahar, Muna S.; Liao, Chunyang; Kannan, Kurunthachalam; Dolinoy, Dana C.; Slitt, Angela L.; Hodgson, Ernest
ABSTRACT Widespread exposure to the endocrine active compound, bisphenol A (BPA), is well documented in humans. A growing body of literature suggests adverse health outcomes associated with varying ranges of exposure to BPA. In the current study, we measured the internal dose of free BPA and conjugated BPA and evaluated gene expression of biotransformation enzymes specific for BPA metabolism in 50 first‐ and second‐trimester human fetal liver samples. Both free BPA and conjugated BPA concentrations varied widely, with free BPA exhibiting three times higher concentrations than conjugated BPA concentrations. As compared to gender‐matched adult liver controls, UDP‐glucuronyltransferase, sulfotransferase, and steroid sulfatase genes exhibited reduced expression whereas β‐glucuronidase mRNA expression remained unchanged in the fetal tissues. This study provides evidence that there is considerable exposure to BPA during human pregnancy and that the capacity for BPA metabolism is altered in the human fetal liver. © 2012 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:116‐123, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21459